2022
DOI: 10.1111/jols.12389
|View full text |Cite
|
Sign up to set email alerts
|

Continuities of exploitation: seasonal migrant workers in German agriculture during the COVID‐19 pandemic

Abstract: Seasonal migrant agricultural workers were declared 'essential' in Germany at the very outset of the COVID-19 pandemic. Two harvest seasons later, continuing poor working conditions, infection outbreaks on farms, and a general exclusion from social security schemes show that the recognition of the 'essential' character of the job has not translated into any improvements for workers.Based on interviews with trade union-affiliated counsellors for migrant workers across Germany and analysis of the policies and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
0
7
0
Order By: Relevance
“…The COVID‐19 pandemic exacerbated the existing inequalities and made them more visible (Bogoeski, 2022; Szelewa & Polakowski, 2022). In Germany, racial categories were mobilised and ‘Eastern Europeans’ were blamed for the spread of the virus across borders (Lewicki, 2023).…”
Section: Experiences Of Racismmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID‐19 pandemic exacerbated the existing inequalities and made them more visible (Bogoeski, 2022; Szelewa & Polakowski, 2022). In Germany, racial categories were mobilised and ‘Eastern Europeans’ were blamed for the spread of the virus across borders (Lewicki, 2023).…”
Section: Experiences Of Racismmentioning
confidence: 99%
“…All these legal forms meet the demand for a workforce that is flexible but cheap, allowing the companies to reduce labour costs. These forms of employment are popular in labour‐intensive sectors such as construction (Kahmann, 2006; Matyska, 2021; Wagner & Hassel, 2015) and food processing (Bogoeski, 2020), but also in agriculture (Bogoeski, 2022) and elder care sector (Leiber et al., 2019; Lutz & Palenga‐Möllenbeck, 2010). For these individuals, contractual employment entails a series of assignments abroad rather than a single assignment (Matyska, 2021).…”
Section: Experiences Of Racismmentioning
confidence: 99%
“…No less importantly, research has shown that attempts to reconcile economic imperatives with sustainability criteria end up detrimental to ecological (Kleinschmit et al 2017) and social concerns. The latter include exploitative working conditions and other forms of domination and injustices in the Global South (Backhouse et al 2021;Puder 2019;Neimark and Healy 2018), or externalization and low-wage migrant labor in bio-based sectors in the North (Prause 2021;Reid et al 2021;Bogoeski 2022). Recent research has also increasingly addressed the bioeconomy in light of unequal North-South relations, e.g., by analytically and empirically unpacking its role in perpetuating and/or deepening ecologically unequal exchange and the production of extractive knowledge (Backhouse et al 2022;Tittor 2021).…”
Section: Transformation Without Transformation: Investigating a Contr...mentioning
confidence: 99%
“…The migrant labour‐intensive sectors faced the risk of major production disruptions due to travel restrictions, supply chain disruptions and worker illness (Clementson, 2020; Organization for Economic Co‐operation and Development, 2020; Schmidhuber & Qiao, 2020). Foreign workers were classified as ‘essential workers’ in many countries so as to be able to create exceptional procedures and regulations for exempting this vulnerable population from immigration, health and labour laws during the pandemic, such as selective border rules for foreign farm workers, differentiated social distancing norms, forced confinement with infected persons, extended working hours, and curfew exceptions (Bogart, 2020; Bogoeski, 2022). Labour‐intensive farms and food production plants became COVID‐19 hotspots, leading to numerous migrant workers catching the virus and dying (Bogart, 2020; Stewart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Labour‐intensive farms and food production plants became COVID‐19 hotspots, leading to numerous migrant workers catching the virus and dying (Bogart, 2020; Stewart et al, 2020). Since the outbreak of the pandemic, the media has highlighted the massive infection outbreaks in the midst of extensive internal and foreign migration of millions of seasonal migrant workers, especially those from indigenous nations and socially marginalised groups, who contend with poor living and working conditions, racism and xenophobia (Bogoeski, 2022; de Pablo et al, 2020; Hennebry & Hari, 2020).…”
Section: Introductionmentioning
confidence: 99%